A Case of Human Leukocyte Antigen (HLA) B27-Positive Intestinal Behçet's Disease with Crohn's Disease-Like Anal Fistulas. Issue 7 (January 2014) - Kobashigawa, Tsuyoshi; Nanke, Yuki; Takazoe, Masakazu; Iihara, Kuniko; Yamanaka, Hisashi; Kotake, Shigeru
A 49-year-old male was admitted to our hospital with complaints of perianal pain, bloody stool, and high-grade fever due to perianal abscess. Drainage was carried out; however, the patient's complaints worsened, and biopsy findings of colonoscopy showed ulcerative colitis-like lesions. The patient was diagnosed as having Behçet's disease with intestinal involvement, did not have HLA-B51, but did have HLA-B27. We describe a case of Behcet's disease with colitis, making a differential diagnosis of inflammatory bowel disease difficult.